Sustainability of Pesantren In The Future: Study of the Charismatic Leadership of Kiai and Leadership Succession of Pesantren in Pekalongan - Ahmad Ta'rifin; Ahmad Halid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study explores the sustainability of pesantren by analyzing the impact of the charismatic leadership of kiai and the succession of leadership within six pesantren in Pekalongan, Indonesia. Grounded in the historical and phenomenological approaches, this research aims to understand how leadership charisma and regeneration influence pesantren continuity. Within the broader discourse of Islamic education, the kiai's role is pivotal, as the pesantren’s vitality often depends on his personal authority and vision. Data were collected through in depth interviews, document analysis, and participant observations, then analyzed using Miles and Huberman's interactive model. The findings reveal that pesantren, which have endured over generations, typically exhibit not only strong charismatic leadership but also structured institutional development and planned leadership succession. Conversely, pesantren that collapsed did so due to the lack of formalization and inadequate regeneration mechanisms. This study contributes to the scholarship of Islamic education by highlighting the crucial interplay between personal charisma, institutional formalization, and leadership continuity. It also suggests that the future sustainability of pesantren requires intentional leadership cultivation and adaptive organizational strategies to secure their relevance amid educational and societal transformations.